Therapeutic Effect of TSG-6 Engineered iPSC-Derived MSCs on Experimental Periodontitis in Rats: A Pilot Study - Yang, Heng; Aprecio, Raydolfo M.; Zhou, Xiaodong; Wang, Qi; Zhang, Wu; Ding, Yi; Li, Yiming (PLOS ONE, 2014)
Background We derived mesenchymal stem cells (MSCs) from rat induced pluripotent stem cells (iPSCs) and transduced them with tumor necrosis factor alpha-stimulated gene-6 (TSG-6), to test whether TSG-6 overexpression would boost the therapeutic effects of iPSC-derived MSCs in experimental periodontitis. Methods A total of 30 female Sprague-Dawley (SD) rats were randomly divided into four groups: healthy control group (Group-N, n = 5), untreated periodontitis group (Group-P, n = 5), iPS-MSCs-treated and iPSC-MSCs/TSG-6-treated periodontitis groups (Group-P1 and P2, n = 10 per group). Experimental periodontitis was established by ligature and infection with Porphyromonas gingivalis around the maxillae first molar bilaterally. MSC-like cells were generated from rat iPSCs, and transducted with TSG-6. iPSC-MSCs or iPSC-MSCs/TSG-6 were administrated to rats in Group-P1 or P2 intravenously and topically, once a week for three weeks. Blood samples were obtained one week post-injection for the analysis of serum pro-inflammatory cytokines. All animals were killed 3 months post-treatment; maxillae were then dissected for histological analysis, tartrate-resistant acid phosphatase (TRAP) staining, and morphological analysis of alveolar bone loss. Results Administration of iPSC-MSC/TSG-6 significantly decreased serum levels of IL-1β and TNF-α in the Group-P2 rats (65.78 pg/ml and 0.56 pg/ml) compared with those in Group-P (168.31 pg/ml and 1.15 pg/ml respectively) (p<0.05). Both alveolar bone loss and the number of TRAP-positive osteoclasts showed a significant decrease in rats that received iPSC-MSC/TSG-6 treatment compared to untreated rats in Group-P (p<0.05), Conclusions We demonstrated that overexpression of TSG-6 in rat iPSC-derived MSCs were capable of decreasing inflammation in experimental periodontitis and inhibiting alveolar bone resorption. This may potentially serve as an alternative stem-cell-based approach in the treatment and regeneration of periodontal tissues.